Konstruksi Nilai Inklusif Tokoh Agama dalam Memandang Pluralitas Agama di Kediri - Khaerul Umam (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
Religious view toward other different groups often lead to conflicts. The ability of a religious person to view differences as a gift shows a high level of religious awareness. However, religious diversity often becomes a challenge when it deals with economic and political interests. Through phenomenological approach, this study aims to see the construction of the inclusive value of religious leaders in Kediri. This research found that the construction of inclusive values has been shaped by three main factors: (1) social culture which improves values ?and norms encouraging individual behaviour and attitudes; (2) historical factors, and (3) religious experience, namely a practice and behavior of the religious leaders.